2016
DOI: 10.1111/jpn.12496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fenugreek seed extract supplementation on growth performance, nutrient digestibility, diarrhoea scores, blood profiles, faecal microflora and faecal noxious gas emission in weanling piglets

Abstract: This study was conducted to evaluate the effect of dietary fenugreek seed extract (FSE) on growth performance, apparent total tract digestibility (ATTD), diarrhoea scores, blood profiles, faecal microflora and faecal gas emission in weanling pigs. A total of 135 weanling pigs [(Yorkshire × Landrace)  × Duroc] with an average BW of (7.96 ± 1.03 kg; 28 days of age) were used in a 42-day study. Piglets were randomly allotted to three experimental diets with nine replicate pens and five pigs per pen. Dietary treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Furthermore, FSE contains soluble dietary fibers (SDF) rich in galactomannan (Bin-Hafeez et al 2002;Khole et al 2014). It has been reported that galactomannan isolated from fenugreek seeds can successfully reduce serum TC (Maisonnier et al 2001;Brummer et al 2003;Hannan et al 2007;Begum et al 2016). In the present study, SDF was not analyzed.…”
Section: Itemsmentioning
confidence: 88%
See 4 more Smart Citations
“…Furthermore, FSE contains soluble dietary fibers (SDF) rich in galactomannan (Bin-Hafeez et al 2002;Khole et al 2014). It has been reported that galactomannan isolated from fenugreek seeds can successfully reduce serum TC (Maisonnier et al 2001;Brummer et al 2003;Hannan et al 2007;Begum et al 2016). In the present study, SDF was not analyzed.…”
Section: Itemsmentioning
confidence: 88%
“…A previous study has indicated that dietary supplementation with plant extracts containing 400 g kg −1 of fenugreek extracts can improve the ADG of nursery pigs (Cho et al 2006). Moreover, it has been reported that FSE supplementation at 2 g kg −1 increased ADG in sows (Hossain et al 2015) and G:F in weanling pigs (Begum et al 2016). Other studies have shown that dietary supplementation with plant extracts containing saponin can improve the growth performance and feed efficacy of broilers (Johnston et al 1981;Griggs and Jacob 2005).…”
Section: Effects Of Fsementioning
confidence: 98%
See 3 more Smart Citations